2012
DOI: 10.1504/ijtel.2012.051583
|View full text |Cite
|
Sign up to set email alerts
|

Erroneous examples: effects on learning fractions in a web-based setting

Abstract: Learning from errors can be a key 21st century competence, especially for informal learning where such metacognitive skills are a prerequisite. We investigate whether, how and when web-based interactive erroneous examples promote such competence, and increase understanding of fractions and learning outcomes. Erroneous examples present students with common errors or misconceptions. Three studies were conducted with students of different grade levels. We compared the cognitive, metacognitive, conceptual, and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Fading instructional support relies on the position that, when the learner is able to carry out the required action, the support should be gradually reduced until it is no longer needed (see Van Merriënboer and Kirschner 2013). Fading is not restricted to one specific pedagogy and has been studied, for example, with regard to collaborative learning (Bouyias and Demetriadis 2012;Tsovaltzi et al 2012;Fischer 2011), inquiry learning (McNeill et al 2006), learning for conceptual change (Biemans and Simons 1996), and worked examples (Renkl and Atkinson 2003;Van Gog and Rummel 2010). Although scientific evidence demonstrates effectiveness of fading for learning in some studies (e.g., Renkl et al 2004;Tsovaltzi et al 2010), results that are mixed (e.g., Leutner 2000;McNeill et al 2006) and even disappointing (e.g., Bouyias and Demetriadis 2012;Wecker et al 2010) are reported as well.…”
Section: Adaptive Fading Of the External Supportmentioning
confidence: 99%
“…Fading instructional support relies on the position that, when the learner is able to carry out the required action, the support should be gradually reduced until it is no longer needed (see Van Merriënboer and Kirschner 2013). Fading is not restricted to one specific pedagogy and has been studied, for example, with regard to collaborative learning (Bouyias and Demetriadis 2012;Tsovaltzi et al 2012;Fischer 2011), inquiry learning (McNeill et al 2006), learning for conceptual change (Biemans and Simons 1996), and worked examples (Renkl and Atkinson 2003;Van Gog and Rummel 2010). Although scientific evidence demonstrates effectiveness of fading for learning in some studies (e.g., Renkl et al 2004;Tsovaltzi et al 2010), results that are mixed (e.g., Leutner 2000;McNeill et al 2006) and even disappointing (e.g., Bouyias and Demetriadis 2012;Wecker et al 2010) are reported as well.…”
Section: Adaptive Fading Of the External Supportmentioning
confidence: 99%
“…As other authors have already acknowledged [2,3], a long list of foundational questions remain to be resolved before any system could be designed that employs deliberate errors and/or facilitates discrepancy detection in a truly adaptive way. Although the current research provides a framework in which to better understand the nature of such errors, further research is needed to address general questions regarding when and how often to deliberately introduce system-side errors, and whether or not they are equally appropriate for all types of learners or all levels of domain proficiency.…”
Section: Extending System-side Errors: Domains Users Unanswered Quementioning
confidence: 99%
“…[2,3]), but arguably draws on the same underlying metacognitive processes of model-comparison and discrepancy detection. Presenting learners with deliberate errors may be a more widely applicable strategy than it initially appears.…”
Section: Extending System-side Errors: Domains Users Unanswered Quementioning
confidence: 99%
See 1 more Smart Citation
“…There is already a small body of existing work on adaptive systems for older, TD children that has begun to explore the use of erroneous worked examples to support metacognition and content learning (e.g. [14]) during explicit problem-solving. In those contexts and in the present one, many general questions remain unanswered regarding when and how often to use discrepancy, and whether or not this strategy is equally appropriate for all learners.…”
Section: Future Workmentioning
confidence: 99%